2005
DOI: 10.1529/biophysj.104.047290
|View full text |Cite
|
Sign up to set email alerts
|

HERG Channel (Dys)function Revealed by Dynamic Action Potential Clamp Technique

Abstract: The human ether-a-go-go-related gene (HERG) encodes the rapid component of the cardiac delayed rectifier potassium current (I(Kr)). Per-Arnt-Sim domain mutations of the HERG channel are linked to type 2 long-QT syndrome. We studied wild-type and/or type 2 long-QT syndrome-associated mutant (R56Q) HERG current (I(HERG)) in HEK-293 cells, at both 23 and 36 degrees C. Conventional voltage-clamp analysis revealed mutation-induced changes in channel kinetics. To assess functional implication(s) of the mutation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 42 publications
10
68
0
5
Order By: Relevance
“…6A, top) showed that hERG R56Q generated a larger outward current than WT hERG channels that peaked earlier during the ramp repolarization phase (Fig. 6, A, C, and D, p Ͻ 0.05), but declined at a faster rate presumably due to its faster deactivation kinetics, similar to what has been previously described (14,24). We next tested whether NPAS rescued changes in resurgent current.…”
Section: Npas Rescues Altered Resurgent Current Generated By a Dynamisupporting
confidence: 59%
See 1 more Smart Citation
“…6A, top) showed that hERG R56Q generated a larger outward current than WT hERG channels that peaked earlier during the ramp repolarization phase (Fig. 6, A, C, and D, p Ͻ 0.05), but declined at a faster rate presumably due to its faster deactivation kinetics, similar to what has been previously described (14,24). We next tested whether NPAS rescued changes in resurgent current.…”
Section: Npas Rescues Altered Resurgent Current Generated By a Dynamisupporting
confidence: 59%
“…The LQT2 mutations we selected were based on previous findings demonstrating that when point mutations were made at the selected residues, either to a LQT2-associated mutation or to alanine, the mutant hERG channels exhibited altered deactivation kinetics in Xenopus oocytes (6,(13)(14)(15). We also included K28E, R56Q, and M124R, which were previously investigated in mammalian cells (22)(23)(24). We first measured functional expression of each hERG PAS-LQT2 channel using whole cell patch clamp recordings ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, R4A/R5A acts in a dominant manner to disrupt the slow kinetics of hERG1 channel deactivation. The LQT2-associated point mutation R56Q, located in the PAS domain of hERG1, was previously reported to increase the rate of channel deactivation when expressed in Xenopus oocytes (8) and to increase the rate of activation and deactivation but not inactivation when channels were heterologously expressed in HEK-293 cells (34). To further explore how a mutation in the PAS domain affects the rate of deactivation, R56Q subunits were placed in either position 1 (R56Q 1 /WT 3 ) or position 3 (WT 2 /R56Q 1 /WT 1 ) of a concatenated tetramer, and the current conducted by these channels was compared with R56Q monomer and R56Q 4 channels.…”
Section: Mutation Of Residues In the N-terminal Domain Of A Single Sumentioning
confidence: 99%
“…The analysed cardiac ionic current is specifically inhibited (or abolished if a model of cardiomyocyte is used) and replaced by an ionic current measured in a cell line, e.g. in the human embryonic kidney (HEK) 293 cells in Berecki et al (2005). On the surface of these cells, only the required ionic channel is expressed, either wild-type or mutant.…”
Section: Dynamic Ap Clampmentioning
confidence: 99%
“…The cell line cell is stimulated with AP waveform continuously recorded from the cardiomyocyte (or generated by the model). Berecki et al (2005) used this technique to readily and unambiguously determine the effect of hERG mutation R56Q (identified in a patient with long QT syndrome) on AP configuration in particular layers of ventricular myocardium. Electrophysiological properties of R56Q-hERG mutation found out with the conventional whole-cell patch clamp technique showed controversial changes of AP duration.…”
Section: Dynamic Ap Clampmentioning
confidence: 99%